Determining the Investment Attractiveness of the Corporation (Economics and region, 2021)
This article explains the core of the concept of corporation providing information on the first ever – created corporations. In addition, the article highlights the importance of assessing the investment attractiveness of borrowers among the actions aimed at reduction of loan risks in the practice of investor corporations. Next, it also presents the important system of indicators in the assessment of investment attractiveness. The reliability of corporations is characterized, above all, by how timely they repair loans. When analyzing the attractiveness of the corporation, the place and role of borrowers in the structure of a corporation must be determined. Regardless of the nature of future credit transactions, identification allows to accurately determine the nature of the corporation's activities, which is reflected in the article. At the end, the article emphasizes the contribution of the action plan associated with investment attractiveness assessment to the resources attractiveness, as well as customs associated with the resource attractiveness.
Keywords: corporation; loan risks; investment attractiveness; formal and informal indicators; economic environment